WAHDAT AL-ADYÃN: SPIRIT KOSMOPOLITANISME DALAM MENJAGA KEUTUHAN NKRI - Elmansyah, Elmansyah (UIN Antasari, 2018)
Symptoms of divisions in the country seem very worrying, due to the five-year political contestation. Religion is used as a tool to gain political advantage, regardless of the negative impacts. This article tries to provide an overview of one of the concepts of Sufism, which can be used as a solution to overcome the divisions. The main objective of this research is to find alternative strategies for the community and government, especially Muslims in facingthe various propagand that want to divide the integrity of the nation. The research method used is descriptive-critical analysis method, with a philosophical approach. The results showed that the spirit of cosmopolitanism in the concept of wahdat al-adya>n from Abu Mansyur Al-Hallaj, could be used as a solution to maintain the integrity of the Unitary Republic of Indonesia (NKRI).